International Context Indonesia's Counter-Terrorism Policy, 2001-2004 - Ali Muhammad (Parahyangan Center for International Studies, 2012)
Terrorism is a serious security problem in Indonesia as indicated by a suicide bomb attack in Solo church and mosque in the Cirebon Police office complex (2011), JW Marriot (2009) and a series of terror attacks before. This article discusses the international context and the implications for the government's counter-terrorism policy. The extent to which international factors affect the government's counter-terrorism policy during the years 2001-2004? This period is considered important because it is a critical period in the war against terrorism. The argument is that global context